Ku teatrowi agonistycznemu. Pippa Delbona Waleczność rycerska w Teatrze San Carlo - Woźniak, Katarzyna (Przestrzenie Teorii, 2021)
The author aims to outline the dramatic work of the Italian director Pippo Delbon as establishing a theater of agon. From the state of research, she analyzes the staging of Pietro Mascagni’s Cavalleria rusticana and formulates the theory of Delbonos’s theater of agon based on M. de Certeau’s and W. Świątkowska’s papers and the theories of dramaturgy of Anna Krajewska and Dariusz Kosiński.